Plasma levels of protachykinin-1 (TAC1) in patients with sarcoidosis - Turan Akdağ; Celalettin Korkmaz (SERNEV, 2020)
Introduction: The etiology and pathogenesis of sarcoidosis, a systemic granulomatous lung disease affecting many people, still remain unknown. Sarcoidosis is diagnosed by demonstrating non-caseous granulomas and ruling out granulomatous diseases. Therefore, sensitive biomarkers used in diagnosis and follow-up processes are needed. Our aim is to investigate diagnostic value of plasma protachykinin-1 (TAC1) levels in sarcoidosis patients.Methods: Forty-two sarcoidosis patients followed-up by the department of chest diseases, and 38 controls were included into the study. Clinical, radiological and laboratory data of patients were recorded, and plasma TAC1 levels were analyzed in patients and healthy controls.Results: Plasma TAC1 levels of sarcoidosis patients and controls were found as 1124.25±1117.25 ng/L and 1319.37±1357.38 ng/L, respectively. Although not statistically significant (p=0.338), a decrease was found in TAC1 levels of sarcoidosis patients. Additionally, patients' lymphocyte levels were also found significantly lower than controls (p=0.007). No statistically significant correlation was found between other laboratory findings, including leukocyte, neutrophil, monocyte, eosinophil count, cluster of differentiation 4 (CD4) CD4 +, CD8 +, bronchoalveolar lavage (BAL) CD4 +, BAL CD8 + and neutrophil/lymphocyte ratio (NLR), and plasma TAC1 levels.Conclusions: To the best of our knowledge, our study is the first to investigate plasma TAC1 levels as a biomarker in sarcoidosis patients. Although plasma TAC1 levels were slightly decreased in sarcoidosis patients, the decrease was not statistically significant, and no adequate data were provided for the use of plasma TAC1 level as a biomarker. We consider more comprehensive research are needed to elucidate the entity.